To Determine the Frequency of Dural Tear in Patients Presenting with Depressed Skull Fracture: An Experience of 96 Cases in a Tertiary Care Hospital - Amir, Sohail; Shah, Syed Amir; Zaman, Khaleeq -Ur- (Journal of Gandhara Medical and Dental Science, 2017)
OBJECTIVE The objective of this study was to determine the frequency of dural tear in patients with depressed skull fractures. MATERIAL and Method This cross-sectional study was conducted in department of Neurosurgery Pakistan institute of Medical Sciences Islamabad from January 2010 to December 2011. All patients of either gender with depressed skull fracture above one year of age were included in the study. CT brain with bone window done in all patients. Per-operative dura in the region of depressed skull fracture was closely observed for any dural tear. The data collected on pre designed proforma. and analyzed using SPSS version 20.0 RESULTS A total of 96 patients were recruited in the study out of which 58(60.4%) were male and 38(39.5%) were female. Male to female ratio was 1.5:1. And mean age was 19.23 + 2.54 years. The most common location of depressed skull fracture was parietal 37(38.5%), followed by frontal in 27(28.1%), 15(15.6%)in temporal region,13(13.5%) in occipital region and only 4(4.1%) located in posterior fossa. Dural tear was present in 33(34.3%) while in 63(65.6%) it was absent. Other finding associated with depressed skull fracture per operatively were extradural hematoma in 16(16%), subdural hematoma in 11(11.4%), contusion in 16(16.6%) and pneumoencephalus was observed in 20(20.8%) cases. CONCLUSION The frequency of dural tear in DFS is quite high, so one should be vigilant to identify the defect and repair it properly to minimize post operative complications.